PPARβ/δ‐agonist GW0742 ameliorates dysfunction in fatty acid oxidation in PSEN1ΔE9 astrocytes. Issue 1 (19th November 2018) - Konttinen, Henna; Gureviciene, Irina; Oksanen, Minna; Grubman, Alexandra; Loppi, Sanna; Huuskonen, Mikko T.; Korhonen, Paula; Lampinen, Riikka; Keuters, Meike; Belaya, Irina; Tanila, Heikki; Kanninen, Katja M.; et al.
Abstract: Astrocytes are the gatekeepers of neuronal energy supply. In neurodegenerative diseases, bioenergetics demand increases and becomes reliant upon fatty acid oxidation as a source of energy. Defective fatty acid oxidation and mitochondrial dysfunctions correlate with hippocampal neurodegeneration and memory deficits in Alzheimer's disease (AD), but it is unclear whether energy metabolism can be targeted to prevent or treat the disease. Here we show for the first time an impairment in fatty acid oxidation in human astrocytes derived from induced pluripotent stem cells of AD patients. The impairment was corrected by treatment with a synthetic peroxisome proliferator activated receptor delta (PPARβ/δ) agonist GW0742 which acts to regulate an array of genes governing cellular metabolism. GW0742 enhanced the expression of CPT1a, the gene encoding for a rate‐limiting enzyme of fatty acid oxidation. Similarly, treatment of a mouse model of AD, the APP/PS1‐mice, with GW0742 increased the expression of Cpt1a and concomitantly reversed memory deficits in a fear conditioning test. Although the GW0742‐treated mice did not show altered astrocytic glial fibrillary acidic protein‐immunoreactivity or reduction in amyloid beta (Aβ) load, GW0742 treatment increased hippocampal neurogenesis and enhanced neuronal differentiation of neuronal progenitor cells. Furthermore, GW0742 prevented Aβ‐induced impairment of long‐term potentiation in hippocampal slices. Collectively, these data suggest that PPARβ/δ‐agonism alleviates AD related deficits through increasing fatty acid oxidation in astrocytes and improves cognition in a transgenic mouse model of AD. Main Points: Alzheimer's disease mutation PSEN1ΔE9 causes impaired fatty acid oxidation in human and murine astrocytes. The deficit is rescued by activation of PPARβ/δ with an agonist, GW0742. GW0742 also improves cognitive deficits of APP/PS1 mice.